Phyllosilicate‐derived Nickel‐cobalt Bimetallic Nanoparticles for the Catalytic Hydrogenation of Imines, Oximes and N‐heteroarenes. Issue 18 (14th August 2020) - Ciotonea, Carmen; Hammi, Nisrine; Dhainaut, Jérémy; Marinova, Maya; Ungureanu, Adrian; El Kadib, Abdelkrim; Michon, Christophe; Royer, Sébastien
Abstract: The development of cost‐effective, noble metal‐free catalytic systems for the hydrogenation of unsaturated aliphatic, aromatic, and heterocyclic compounds is fundamental for future valorization of general feedstock. With this aim, we report here the preparation of highly dispersed bimetallic Ni/Co nanoparticles (NPs), by a one‐pot deposition‐precipitation of Ni and Co phases onto mesoporous SBA‐15 silica. By adjusting the chemical composition in the starting mixture, three supported catalysts with different Ni to Co weight ratios were obtained, which were further subjected to treatments under reducing conditions at high temperatures. Characterization of the resulting solids evidenced a homogenous distribution of Ni and Co elements forming the NPs, the best results being obtained for Ni/Co‐2 : 2 samples, for which 50 wt.% Ni–50 wt.% Co NPs are found located on the surface of the residual phyllosilicate. Ni/Co‐2 : 2, presenting the best performances for the hydrogenation of 2‐methyl‐quinoline, was further evaluated in the catalytic hydrogenation of selected imines, oximes and N‐heteroarenes. Due to the high dispersion of bimetallic Ni−Co NPs, excellent properties (activity and selectivity) in the conversion of the selected substrates are reported. Abstract : Pulling your weight : Silica supported bimetallic nickel/cobalt nanoparticles are produced from phyllosilicates reduction obtained by deposition precipitation over SBA‐15. The catalysts were applied to the hydrogenation of imines, oximes and N‐heteroarenes, displaying high activities and selectivities.